Biogas to liquefied biomethane via cryogenic upgrading technologies. (August 2018) - Pellegrini, Laura Annamaria; De Guido, Giorgia; Langé, Stefano
Abstract: Liquid biomethane (LBM), also referred to as liquid biogas (LBG), is a promising biofuel for transport that can be obtained from upgrading and liquefaction of biogas. With respect to fossil fuels, LBM is a renewable resource, it can be produced almost everywhere, and it is a carbon neutral fuel. LBM is 3 times more energy dense than compressed biomethane (CBM) and it allows longer vehicle autonomy. LBM has also a higher energy density than other transport biofuels, it is produced from wastes and recycled material without being in competition with food production, and it assures a high final energy/primary energy ratio. The low temperatures at which LBM is obtained strongly suggest the use of cryogenic/low-temperature technologies also for biogas upgrading. In this respect, since biogas can be considered as a "particular" natural gas with a high CO2 content, the results available in the literature on natural gas purification can be taken into account, which prove that cryogenic/low-temperature technologies and, in particular, low-temperature distillation are less energy consuming when compared with traditional technologies, such as amine washing, for CO2 removal from natural gas streams at high CO2 content. Low-temperature purification processes allow the direct production of a biomethane stream at high purity and at low temperature, suitable conditions for the direct synergistic integration with biogas cryogenic liquefaction processes, while CO2 is obtained in liquid phase and under pressure. In this way, it can be easily pumped for transportation, avoiding significant compression costs as for classical CO2 capture units (where carbon dioxide is discharged in gas phase and at atmospheric pressure). In this paper, three natural gas low-temperature purification technologies have been modelled and their performances have been evaluated through an energy consumption analysis and a comparison with the amine washing process in terms of the equivalent amount of methane required for the upgrading, proving the profitability of cryogenic/low-temperature technologies. Specifically, the Ryan-Holmes, the dual pressure low-temperature distillation process and the anti-sublimation process have been considered. It has been found that the dual pressure low-temperature distillation scheme reaches the highest thermodynamic performances, resulting in the lowest equivalent methane requirement with respect to the other configurations. Highlights: Biogas upgrading is studied for the production of liquid biomethane. Low-temperature technologies and conventional amine scrubbing are compared. The comparison is based on an energy analysis. Low-temperature upgrading technologies perform better than conventional ones.